Why Females Do Better: The X Chromosomal TLR7 Gene-Dose Effect in COVID-19 - Spiering, Anna E.; de Vries, Teun J. (Frontiers in Immunology, 2021)
In the COVID-19 pandemic, a male bias in hospitalization and mortality has become apparent. Males are 2.84 times more often admitted to the ICU and mortality is 1.39 times higher as a result of COVID-19. Various factors play a role in this, and novel studies suggest that gene-dose of Toll-Like Receptor (TLR) 7, one of the crucial pattern recognition receptors for SARS-CoV-2 RNA, could contribute to the sex-skewed severity. This gene is localized on the X chromosome and female immune cells with X-chromosome inactivation (XCI) escape of this gene have biallelic TLR7 expression. As a consequence, these immune cells may produce more type 1 interferon (IFN) upon TLR7 stimulation. In COVID-19, TLR7 is the PPR that causes IFN production. A delayed IFN response has been associated with immunopathogenesis and mortality. Here, we provide a hypothesis that females may be protected against severe COVID-19, due to the biallelic TLR7 expression, allowing them to mount a stronger and more protective IFN response early after infection. Studies exploring COVID-19 treatment via the TLR7-mediated IFN pathway should consider this sex difference. Various factors such as age, sex hormones and escape modulation remain to be investigated concerning the TLR7 gene-dose effect. Other X-linked immune genes are discussed in the context of the COVID-19 sex bias.